Performance Evaluation of Simple Regular Buildings using FBD and DDBD Methods with a Consistent Target Drift - Pamuda Pudjisuryadi; William Sumargo; Alvin Kho; Benjamin Lumantarna (Institute of Research and Community Outreach - Petra Christian University, 2025)
The Direct Displacement Based Design (DDBD) method, proposed by Priestley, is an alternative to the traditional Force-Based Design (FBD) method for earthquake-resistant design. This study compares the performance of 4-story and 12-story buildings designed using both FBD and DDBD with the same target drift of 2%. The differences in base shear used for the design of the two approaches are discussed. To evaluate the buildings' performance, Nonlinear Dynamic Procedure (NDP) analysis, or nonlinear time history analysis, was conducted considering 500 and 2500 years return period earthquakes. The results indicate that the actual drift of both designs deviates from the target drift; however, the observed drifts remain within the maximum limits set by FEMA 356. Moreover, plastic damages were observed in unexpected areas of the columns, suggesting that the strong-column weak-beam design concept, as stipulated by building codes, does not entirely prevent damage to columns.